Diversity and emergence of new variants of African swine fever virus Genotype I circulating in domestic pigs in Nigeria (2016–2018). Issue 2 (15th November 2022) - Masembe, C.; Adedeji, A. J.; Jambol, A. R.; Weka, R.; Muwanika, V.; Luka, P. D.
Abstract: Background: African swine fever (ASF) is the most lethal disease of pigs caused by ASF virus (ASFV) with severe economic implications and threat to the swine industry in endemic countries. Between 2016 and 2018, several ASF outbreaks were reported throughout pig producing states in Nigeria. Objectives: Thereafter, this study was designed to identify the ASFV genotypes responsible for these outbreaks within the study period (2016–2018). Methods: Twenty‐two ASFV‐positive samples by polymerase chain reaction were selected. The samples were collected during passive surveillance in eight states of Nigeria were characterised using 3 partial genes sequences of the virus namely, p72 capsid protein of the B646L, p54 envelope protein of E183L and the central variable region (CVR) within B602L of ASFV. Results: Phylogenetic and sequences analysis based on p72 and p54 revealed ASFV genotype I as the circulating virus. Sequence analysis of the CVR of B602L revealed genetic variations with six ASFV tandem repeat sequence (TRS) variants namely, Tet‐15, Tet‐20a, Tet‐21b, Tet‐27, Tet‐31 and Tet‐34, thus increasing the overall genetic diversity of ASFV in Nigeria. Three of the TRS variants, Tet‐21b, Tet‐31 and Tet‐34, were identified for the first time in Nigeria. The new TRS variants of ASFV genotype I were identified in Enugu, Imo, Plateau and Taraba states, while co‐circulation of multiple variants of ASFV genotype I was recorded in Plateau and Benue states. Conclusions: The high genetic diversity, emergence and increasing recovery of new variants of genotype I in Nigeria should be a concern given that ASFV is a relatively stable DNA virus. The epidemiological implications of these findings require further investigation. Abstract : Three partial genes sequences p72 capsid protein of the B646L, p54 envelope protein of E183L, and the central variable region (CVR) within B602L of African swine fever virus from Nigeria were characterised. We found an increase in tandem repeat sequence (TRS) variants, and three variants (Tet‐21b, Tet‐31 and Tet‐34) were identified for the first time in Nigeria.